2015
DOI: 10.1038/nature14586
|View full text |Cite
|
Sign up to set email alerts
|

DNA rendering of polyhedral meshes at the nanoscale

Abstract: It was first suggested 1 more than 30 years ago that Watson-Crick base pairing might be used to rationally design nanoscale structures from nucleic acids. Since then, and especially since introduction of the origami technique 2 , DNA nanotechnology has seen astonishing developments and increasingly more complex structures are being produced [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . But even though general approaches for creating DNA origami polygonal meshes and design software are available 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
623
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 602 publications
(626 citation statements)
references
References 40 publications
(40 reference statements)
2
623
1
Order By: Relevance
“…6−14 New software also makes designing large nanostructures with tailored properties easier than ever. 15,16 Some of these synthetic structures are static and include crystals, 17−19 polyhedra, 12,20−25 wire-frame designs, 11,26,27 and topological structures such as mobius strips, 28 while others are "active" systems that include walkers, 29,30 gears and hinges, 31 robots, 32,33 and crank-sliders. 34 However, having total control over the structural as well as time-dependent properties of selfassembled DNA nanostructures remains a significant design challenge.…”
mentioning
confidence: 99%
“…6−14 New software also makes designing large nanostructures with tailored properties easier than ever. 15,16 Some of these synthetic structures are static and include crystals, 17−19 polyhedra, 12,20−25 wire-frame designs, 11,26,27 and topological structures such as mobius strips, 28 while others are "active" systems that include walkers, 29,30 gears and hinges, 31 robots, 32,33 and crank-sliders. 34 However, having total control over the structural as well as time-dependent properties of selfassembled DNA nanostructures remains a significant design challenge.…”
mentioning
confidence: 99%
“…This conventional design strategy was turned on its head last year by the first topdown software for building wireframe DNA nanoarchitectures 7 . The software vHelix 7 is based on selecting a target shape that fits to the length of the available scaffold and subsequently creating a polyhedral meshwork of the object-an approach well known in computer graphics.…”
Section: Automated Design Of Dna Origami Veikko Linko and Mauri A Kostmentioning
confidence: 99%
“…1a). The wireframe motif is based on two interconnected DNA double helices (i.e., doublecrossover (DX) molecules), allowing more structural robustness than the previously reported topdown objects with single duplex edges 7 . After designing the shape and obtaining the sequences, researchers fabricate the structures using standard annealing routines.…”
Section: Automated Design Of Dna Origami Veikko Linko and Mauri A Kostmentioning
confidence: 99%
“…Almost at the same time, Högberg et al and Schmidt et al, independently, presented a general method to fold arbitrary 3D DNA structures with trigonal mesh elements, and most of the edges of the meshes were single duplexes (thus suitable for experiments in low ionic-strength environments). [49,50] More recently, Bathe et al demonstrated a generalizable top-down strategy towards an inverse sequence design of DNA origami based on a target shape ( Figure 4E). [51] This allows a fully automatic sequence generation by a computer program with significantly facilitated synthesis of nearly arbitrary wireframe DNA architectures.…”
Section: Tile-based Assemblymentioning
confidence: 99%
“…This technique has offered DNA nanotechnologists unlimited imaginations to create nearly arbitrary shapes on the nanoscale towards various possible applications. [44][45][46][47][48][49][50][51] In addition, because the sequence of the scaffold M13 strand is known, intellectual burden during the design of a complex DNA structure is greatly reduced with the aid of a properly written computer program.…”
Section: Tile-based Assemblymentioning
confidence: 99%